PScore - Ahmad Darawsheh; Mohammad Khaled (My University, 2024)
Our application offers a way to improve sports in Palestine. Our application is used by athletic individuals like football players to advance their careers. Users can showcase their skills and stats on this app to help them become professionals in the future. The application has several types of users: players,managers, stadium owners, admin, and scouts. The player profile contains information such as the player’s position (striker, goalkeeper, defender), stats like goals. The stadium page contains stadium information like location and size. As a player, you can reserve the stadium to play matches instead of the traditional method. Multiple players can reserve the stadium, and the number of reservations allowed depends on the stadium size/type (11 players, 7 players, 5 players per team). Users can view matches that players have reserved, as well as results. Additionally, they can mark players and stadiums as favorites. The application also includes features such as a news page, profile page, login and register functionality, player teams, videos showcasing player skills, player stats (e.g., goals), user types and stadiums. Live score by volunteers (the score of the match): In our country, there’s no API available for accessing the scoreboard or any necessary information about a match. Therefore, we will create our own API. Typical users of the app will watch a match, and if a team scores a goal, those users can report it. The app will consider this reported information as accurate. Additionally, there will be a ranking system where users who provide accurate information will earn credit points. These points will determine whether they become special users, trusted for the information they provide, or remain normal users with standard points. IV